Exploring the Power of Storytelling: Enhancing Engagement and Learning Outcomes Among Adolescents - Shofiyyah, Nilna Azizatus; Asep Muharam; Illa Susanti; Anne Nurdiana (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research aims to explore the utilization of storytelling methods in adolescent learning, with a specific focus on enhancing engagement and learning outcomes. The research methodology employed is a literature review. In the process of data collection, the researcher meticulously gathered and analyzed diverse literature sources about the use of storytelling in adolescent education. The analyzed data sources encompassed scrutiny of scholarly journals, textbooks, and relevant research articles. Previous research findings indicate that storytelling methods can effectively enhance student engagement and deepen their understanding in the learning process. However, research specifically delving into the application of storytelling methods in adolescents remains limited. Consequently, this study aspires to provide a more profound understanding of how storytelling methods can be effectively implemented in the context of adolescent education. Through the literature review methodology, the researcher identified pertinent information, conducted a thorough analysis, and presented valuable findings. This research contributes to the development of compelling and meaningful learning strategies for adolescents. The anticipated outcome of this study is to offer valuable insights for educators and education practitioners in supporting adolescent engagement and learning outcomes through the utilization of storytelling methods